Uncovering temperature-dependent exciton-polariton relaxation mechanisms in hybrid organic-inorganic perovskites - Madeleine Laitz; Alexander E. K. Kaplan; Jude Deschamps; Ulugbek Barotov; Andrew H. Proppe; Inés García-Benito; Anna Osherov; Giulia Grancini; Dane W. deQuilettes; Keith A. Nelson; Moungi G. Bawendi; Vladimir Bulović (Nature Communications, 2023)
Abstract Hybrid perovskites have emerged as a promising material candidate for exciton-polariton (polariton) optoelectronics. Thermodynamically, low-threshold Bose-Einstein condensation requires efficient scattering to the polariton energy dispersion minimum, and many applications demand precise control of polariton interactions. Thus far, the primary mechanisms by which polaritons relax in perovskites remains unclear. In this work, we perform temperature-dependent measurements of polaritons in low-dimensional perovskite wedged microcavities achieving a Rabi splitting of $${{{\hslash }}Ω }_{Rabi}$$ ℏ Ω R a b i = 260 ± 5 meV. We change the Hopfield coefficients by moving the optical excitation along the cavity wedge and thus tune the strength of the primary polariton relaxation mechanisms in this material. We observe the polariton bottleneck regime and show that it can be overcome by harnessing the interplay between the different excitonic species whose corresponding dynamics are modified by strong coupling. This work provides an understanding of polariton relaxation in perovskites benefiting from efficient, material-specific relaxation pathways and intracavity pumping schemes from thermally brightened excitonic species.